Designing Of E-Qiraat Courseware In Empowering Special Class On Reading And Memorizing Al-Quran Skill (Kkq) At Secondary School Level In Malaysia - Ahmad Zulfiqar Shah Abdul Hadi, Mohd Abdul Nasir Abdul Latif , Muhammad Hasbi Abdul Rahman, Mohd Aderi Che Noh (International Journal of Advanced Science and Technology, 2020)
The development of computerized technology has transformed teaching and learning scenarios in the classroom. It has become an essential learning tool to improve and enhance the quality of teaching and learning process. Hence, teaching and learning for Qiraat studies particularly in Special Class on Reading and Memorizing Al-Quran Skill (KKQ) must also have to be upgraded through computerized information visualization technology. This article aims to design computerized information visualization for Qiraat studies. Then, this courseware will be assessed through perceptions of students and teachers based on four aspects namely the design, ease of use, compatibility of information and satisfaction. This study combines three methodologies that are qualitative, quantitative and product design and development. The qualitative study involves the review of the KKQ Qiraat syllabus and some basic information. Quantitative research involves the assessment of the user acceptance and effectiveness of which teachers and students on the designs produced. While the study product development will use the ADDIE (Analyze, Design, Development, Implement, Evaluation) approach which is for instructional technology in the production of educational products. The results indicated that students and teachers accept this courseware in the form of its design, ease of use, compatibility of information and satisfaction of use. Hence, advanced studies in the context of the development of teaching and learning in Qiraat can still be explored in the future to ensure the quality of Qiraat studies.